EFFECT OF SOIL SALINITY LEVELS ON PHYTOGORMONE BALANCE IN POTATO ADAPTATION - Saidov Madilkhan Azizkhanovich; Almamatov Bahromjon Uktamovich (American Journal Of Agriculture And Horticulture Innovations, 2023)
The comprehensive study of changes in the content of cytokinins, indole acetic acid (IAA) and abscisic acid ABA, growth rates, and development of potatoes during soil salinity NaCl. Studies have shown that the hormonal balance of potato organs throughout ontogenesis under the influence of NaCl salinity undergoes significant changes: the content of cytokines and auxins decreases, the level of ABA increases, as a result, the ratio of cytokines +IAA/ABA falls. These changes in the hormonal balance are not only the result of a stress response but also have an adaptive value. The conducted research allowed us to find out the relationship between changes in hormonal balance and physiological processes.